2022
DOI: 10.1891/cl-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oral Feeding Methods in Preterm Infants on Transition to Direct-Breastfeeding and Discharge Time: A Retrospective Cohort Design

Abstract: BACKGROUNDThe most common alternatives in feeding preterm infants are bottle feeding and cup feeding. However, there is no clear and precise clinical evidence to show the superiority of a single method. New studies are needed to eliminate confusion on this subject.AIMThe effects of oral feeding methods on the transition to direct-breastfeeding and length of stay in preterm infants.METHODSThis retrospective study was carried out in a single NICU. Data was collected from the digital records and correlated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Çamur et al [ 27 ] reported that the bottle and cup feeding methods were equally effective in reaching the time of full oral feeding and there was no statistically significant difference between the mentioned groups. However, the study results of Say et al [ 19 ] illustrated that the transition time to full oral feeding was significantly shorter in syringe-fed preterm neonate’s compared to bottle-fed preterm neonate’s.…”
Section: Discussionmentioning
confidence: 99%
“…Çamur et al [ 27 ] reported that the bottle and cup feeding methods were equally effective in reaching the time of full oral feeding and there was no statistically significant difference between the mentioned groups. However, the study results of Say et al [ 19 ] illustrated that the transition time to full oral feeding was significantly shorter in syringe-fed preterm neonate’s compared to bottle-fed preterm neonate’s.…”
Section: Discussionmentioning
confidence: 99%